Spatial patterns models to support the Portuguese maritime spatial planning - Fernandes, Maria da Luz Bandeira Rodrigues (2021)
Sea space is increasingly occupied and leading to rising pressures on species and habitats. Marine and coastal policy framework is acknowledging this fact and using Maritime Spatial Planning (MSP) as a tool for achieving a better integrated management and planning of maritime spaces. The European Directive on Maritime Spatial Planning (Directive 2014/89/EU) aims to achieve an integrated approach to marine governance, whilst securing and maintaining the healthy status of marine and coastal waters, following an Ecosystem Based Management Approach (EBM). Moreover, Member States must produce plans until 2021. In 2014, Portugal enacted the law establishing the Basis of the National Maritime Space and in 2015 followed the framework for elaboration of the national Maritime Spatial Plan, named as Situation Plan. The Portuguese Situation Plan, developed for Mainland, Madeira and Extended Platform Subdivisions was approved in December 2019. This thesis’ main contribution is the development of a set of spatial patterns for addressing coasts and seas with comparable information, moving away from the sectorial approach to the sea. The patterns are used to classify maritime spaces and gather evidence on potentials opportunities and challenges for the development of regions. Therefore, this thesis develops methodological approaches for planners and managers to support the MSP process in a time and resource data limited setting using the Portuguese Mainland Subdivision as a case study. The approaches are easy to use, accessible and easily understood by planners and decision-makers. Most of the outputs were produced in the forms of maps showing combined information, and in some cases, different scenarios for selection of best available options. The focus was given to environmental impacts conservation and socio-ecological assessment in line with an EBM approach. The tools presented in this thesis can be of value in the years to come to provide MSP with relevant information to support an EBM approach to the sea management of ocean uses.